Towards a compulsory curriculum - White, J. P. (London : Routledge, 2012)
Written prior to the introduction of the national curriculum, this volume argued for precisely that: a broad framework of a compulsory education at national level for all schools. The author considers the question of the content of his proposed compulsory curriculum in terms of principles derived from a fundamental ethical position and from an analysis of kinds of human activity that seeks to establish important educational priorities. The discussion covers arguments concerning intrinsically worthwhile activities, the need for a practical component of the curriculum and the priority that hu.
Bibliography and index.
Keywords: Education and state; Education -- Curricula -- Great Britain; Education -- Standards -- Government policy -- Great Britain